Effects of a recommended training program on some complex feints and some physical variables in junior Japanese handball players - Taha Yahia, S. A.; Tanaka, M. (World Journal of Sport Sciences, 2010)
The current research aims at designing a training program for some complex feints with the ball in junior Japanese handball players and identifying the effects of this program on some physical variables and performance level (duration-performance) and complex feints with the ball in junior Japanese handball players. The researchers used the quasi-experimental approach with one-group design and pre-/postmeasurement. Sample was purposefully chosen from Japanese junior handball players-Faculty of Sports and Health Science-Fukuoka University-Japan. Sample included 40 junior players (born in 1988-1989-1990). The researchers concluded that the recommended training program had a positive effect on the post-tests of the experimental group on physical variable, with improvement percentage 1.11-15.64%, skills variables (feint duration) with improvement percentage 2.99-10.35% and ills variables (feint performance) with improvement percentage 22.39-45.59%.